Umur ibu dan kejadian persalinan seksio caesaria pada primipara - Estu Tri Haryati; Asmar Yetty Zein; Niken Meilani (Poltekkes Kemenkes Yogyakarta, 2013)
According to the World Health organization (WHO), the section caesarian (sc) stated that delivery is approximately 10-15% of all birth is developing countries. In Indonesia, the prevalence of maternal mortality primiparous as many as 230 people from 750 primiparous mother. While the prevalence of maternal primipara with SC in Panembahan Senopati Hospital has increased from the 2010 amounted to 26.87%, in 2011 was 28,94%, and in 2012 increased by 33.59% from 1652 deliveries. Obtained result shows primiparous mothers with SC delivery in Panembahan Senopati Hospital in 2011-2012 majority maternal age risk in case subject and 19.8% risk of maternal age in control subject 49.2%. with maternal age risk of having a relationship with the incidence of SC with a value of p-value 0.000 <0,05 with a percentage of 19.8% and has a close relationship 0.306